2021
DOI: 10.1002/ctm2.551
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the immune landscapes of advanced ovarian cancer in an optimized in vivo model

Abstract: Background Ovarian cancer (OC) is typically diagnosed late, associated with high rates of metastasis and the onset of ascites during late stage disease. Understanding the tumor microenvironment and how it impacts the efficacy of current treatments, including immunotherapies, needs effective in vivo models that are fully characterized. In particular, understanding the role of immune cells within the tumor and ascitic fluid could provide important insights into why OC fails to respond to immunothera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 116 publications
1
3
0
Order By: Relevance
“…These results are similar to migration indices observed in transwell coculture assays with ovarian cancer cells and macrophages [14]. Furthermore, previous in vivo studies have shown that ID8 tumor models can be characterized by enrichment of macrophages in tumor nodules [15]. The recruitment of macrophages by ovarian cancer cells in our model is therefore reflective of previous in vivo and in vitro studies.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These results are similar to migration indices observed in transwell coculture assays with ovarian cancer cells and macrophages [14]. Furthermore, previous in vivo studies have shown that ID8 tumor models can be characterized by enrichment of macrophages in tumor nodules [15]. The recruitment of macrophages by ovarian cancer cells in our model is therefore reflective of previous in vivo and in vitro studies.…”
Section: Discussionsupporting
confidence: 89%
“…ID8 is a well-characterized model of ovarian cancer that was derived from C57/BL/6 ovarian epithelium. Specifically, ID8 is an aggressive model that establishes in vivo microenvironments that are infiltrated by macrophages [15]. Without tumor cells, the presence of macrophages within the gel region was 56 ± 6 x 10 -5 cells/px 2 .…”
Section: Ovarian Cancer Secreted Factors Promote Macrophage Recruitme...mentioning
confidence: 99%
“…While 3D culture systems are gaining momentum in the development of cancer therapeutics 66 preclinical studies would provide evidence of the anti-cancer potential of AF- and CV-MSCs (and their secretome) in a system that more closely recapitulates the complexity of the tumor microenvironment. We anticipate, however, that building on this work, future studies evaluating the anti-cancer potential of the secretome of AF- and CV-MSCs will be performed in mouse models of syngeneic ovarian cancer optimized in the lab 67 to provide additional insights on the biological effect in complex systems. Finally, moving forward, we are committed to providing a comprehensive characterization (in terms of proteomic, lipidomic, and transcriptomic profile) of the exosomes released by AF- and CV-MSCs, to identify specific targeting moieties as well as master regulators of the cytotoxic and inhibitory effect observed.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…Indeed, metastasis is rarely observed in most subcutaneous mouse models, including OC. 12 , 13 The in vivo metastatic OC models currently used mainly refer to the intraperitoneal 14 and orthotopic models. 15 The intraperitoneal model is able to recapitulate the implantation metastasis of OC at advanced stages, but it is generated without primary tumor growth.…”
Section: Introductionmentioning
confidence: 99%